STRATEGI INTERVENSI KEPERAWATAN UNTUK MENGURANGI KECEMASAN IBU POSTPARTUM KARENA PERAWATAN TERPISAH: SYSTEMATIC REVIEW - Chairunisa, Navira; Rachmawati, Imami Nur; Rahmah, Hayuni (Media Penelitian dan Pengembangan Kesehatan, 2024)
Separate care between mother and newborn in the postpartum period often has an impact on the psychological condition of the postpartum mother. This psychological condition is not only caused by the health condition of the newborn but is also affected by the loss of the role of a mother. This study aimed to examine the effectiveness of nursing interventions to reduce postpartum maternal anxiety due to separate treatments. The design of this research is a systematic review. This study systematically reviewed RCT studies using the electronic databases PubMed, EMBASE, Scopus, Proquest, Sage, Clinical Key, and a reference list of articles for RCT studies published from January 2013 to October 2023 on nursing interventions against postpartum maternal anxiety that were not hospitalized, assessment of article quality using JBI Critical Appraisal Tools for RCT. A total of 11 research articles met the criteria and were assessed for quality. Consistent results in this review showed that overall, three categories of maternal empowerment and education interventions (p 0.001), music (p <0.05), and relaxation (p 0.003) were shown to be effective in reducing postpartum anxiety due to separate treatments. The main findings of this study showed that nursing interventions that are effective in reducing maternal anxiety are maternal empowerment and education programs, relaxation, and music therapy that are carried out gradually and continuously.